‘Infidels’ on the Internet: Pakistan’s Social Media ‘Cancel Culture’ During the Pandemic - Uddin, Sadia (Imaginations)

(untitled) (York University, 2023)
This paper explores how the pandemic intersects with religious nationalism in Pakistan and isolates vulnerable groups through the use of its colonial-era Blasphemy Laws. Using the August 2020 case of a music video shoot inside a mosque, the paper emphasizes the role of social media ‘cancel culture’ in mobilizing these laws to persecute ‘wrongdoers’ in the name of ‘Islam’. The paper confronts power relations and creates new knowledge to challenge prevailing hegemonic structures by exploring the selective applicability of cancel culture and the Blasphemy Laws.